SENTUHAN ARSITEKTUR NUSANTARA PADA ILMU KONSTRUKSI BANGUNAN, STRATEGI MENINGKATKAN KUALITAS PENGAJARAN SECARA DARING - Ch. Koesmartadi; Gustav Anandhita (ATRIUM: Jurnal Arsitektur, 2020)
Title: A Nusantara Architecture Touch on Building Construction Science: A Strategy to  Improve Quality for Online Teaching Covid-19 pandemic hit the world hard, causing so many pedagogical reconfiguration and alteration that forces the world of education to change its approach, particularly in the applied science of architectural. This shift seems to be positive in terms of time available to rediscover and realign its relevance towards local wisdom. Visual communication during online class appears to be more interesting due to its capability to showcasing appealing sketch on PC/laptop or smartphone. This situation gives teacher and lecturer even greater chance to accommodate in-depth local construction materials. In order to achieve better formula, innovation are needed to boost visual appeal. By using online devices, students are capable of capitalizing features which ensure their understanding and focus through 3-D structures and visualization, especially towards roof that has been an instrumental character of Nusantara Architecture.